Breast Cancer Subtypes in Patients Aged 70 Years and Older. (27th May 2016) - Königsberg, Robert; Pfeiler, Georg; Hammerschmid, Nicole; Holub, Oliver; Glössmann, Kerstin; Larcher-Senn, Julian; Dittrich, Christian
ABSTRACT: Recurrence and survival pattern in breast cancer (bc) patients (pts) ≥ 70 years subcategorized according to subtype and age are still an area of uncertainty. Tumor characteristics, patient demographics, therapies applied, and recurrence pattern were compared between luminal A (LA), luminal B (LB), Her2/neu overexpressing (Her+) and triple-negative (TN) bc subtypes and the age subcategories 70–74, 75–79, ≥80 years. Based on univariate Cox-regression-analyses distant-disease-free-survival (DDFS) differed significantly for bc subtypes ( p = 0.0002), notably for Her+ vs. LA ( p = 0.0014), TN vs. LA ( p < 0.001), and TN vs. LB ( p = 0.0086). Not age, but Her+ and TN represented prognostic factors for DDFS.